Smallholder demand for maize hybrids and selective seed subsidies in Zambia - Smale, Melinda; Birol, Ekin (International Food Policy Research Institute, 2013)
This analysis explores smallholder demand for hybrid maize seed by subsidy receipt. We test the hypothesis that the hybrid maize subsidy in Zambia is selectively biased due in part to its delivery mechanism and the self-selection of farmers who are able or choose to exercise their claim. Our analysis found that farmers with a lower poverty headcount are more likely to receive subsidized seed. In addition, a segment of farmers with a high predicted demand for hybrid seed are not reached by FISP—and they are poorer in terms of land and income than those who obtain the subsidy. These farmers represent a potentially important demand segment for HarvestPlus, which might consider addressing their needs through means other than a subsidy program.